Electronic transport theories : from weakly to strongly correlated materials - Singh, Navinder, 1977 (Boca Raton, Fla. : CRC Press, Taylor & Francis Group, 2017)
The issue of transport in strongly correlated materials is of current interest. This book presents a concise and pedagogical introduction to a wide range of topics in electronic transport. There are plenty of books that cover the traditional theories (Boltzamnn transport equation and Kubo formula) however, there is no such book that covers the traditional theories along with the recent theories of transport in strongly correlated materials. Being useful to both graduates and researchers, this book deals with the challenging problems in this area--
1. Introduction and objective of the study -- 2. The traditional Boltzmann equation based approaches -- 3. Some techniques from nonequilibrium statistical mechanics -- 4. The Zwanzig-Mori-Gotze-Wolfle memory function formalism -- 5. The Kohn-Luttinger theory : quantum mechanical basis of the Bloch-Boltzmann equation -- 6. Strange metals : a survey -- 7. Electronic transport theories from simple to strange metals : a summary -- 8. Supporting material and practice exercises.
Keywords: Electron transport; Transport theory; Nonequilibrium statistical mechanics